Radio: The Indigenous Peoples Media Construction of the Concept of Na-tion - Avengoza-Almadrones, Rosalie J. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study explored whether radio had an impact on the indigenous peoples or Bihug of Camarines Norte, Philippines in developing their concept of nation. Descriptive and exploratory research designs were used. Through a multi-level approach, the intensive qualitative component of the research procedure was addressed, the construction of the indigenous peoples’ concept of nation through radio listening. Thematic analysis was used to process the data gathered. The study employed Anderson’s theory on imagined communities as a social construction and Crisell’s characteristics of radio. Radio in the community of the indigenous peoples did not appear to play a primary role in the construction of their concept of nation; rather their actual encounters with people in various activities, their knowledge of places, the recognition given to their benefactors and stories from ancestors which helped in the realization of the extent of their assimilation with the lowlanders, their being Filipino, and their membership of a minority group were the main contributory factors. Although radio was not the main source, it contributed to the formation of their concept of nation as events, places, sense of belongingness, and benefactors. This study, which dealt with the role of radio in the formation of the indigenous peoples’ concept of nation in Camarines Norte, Philippines also considered other factors which may influence the construction of a concept of nation aside from radio like other mass media, and their social encounters with members of NGOs, other agencies and institutions, barangay officials and the constituents of the community where they stay.